Hemorrhagic Stroke in Atrial Fibrillation: Trends in Incidence, Case Fatality, and Prior Oral Anticoagulation - Tiili, Paula; Lehto, Mika; Halminen, Olli; Haukka, Jari; Lehtonen, Ossi; Linna, Miika; Satopää, Jarno; Korja, Miikka; Niemela, Mika; Kinnunen, Janne; Aro, Aapo L.; Mustonen, Pirjo; et al. (Ovid Technologies (Wolters Kluwer Health), 2025)
Background: Despite increased atrial fibrillation (AF) and oral anticoagulation (OAC) use among patients with intracerebral hemorrhage, trends in hemorrhagic stroke (HS) incidence in AF remain unclear. We examined recent epidemiological trends, considering advances in stroke prevention and an aging population.
Methods and results: A Finnish nationwide study using linked administrative registries followed 168 121 patients with incident AF (2009-2017) until the first-ever intracerebral or subarachnoid hemorrhage, death, or study end (November 2018). HS incidence rates, the proportion of fatal cases (case fatality rate %), and anticoagulant purchases within 90 days before HS were analyzed. Temporal trends were assessed using logistic and Poisson regression. A total of 1890 patients with AF (53% women, median age 80.2) experienced their first-ever HS. The average annual incidence rate was 2.82/1000 PY (95% CI, 2.72-2.92), remaining stable over 10 years (range 2.62-3.22). Age-standardized incidence rates were 2.65 (2.48-2.82) for women and 2.94 (2.70-3.15) for men. The annual case fatality rate averaged 46.5% (43.9%-49.1%) without notable temporal or sex differences. Older age was associated with higher incidence rates and case fatality rate, with an increasing proportion of patients over 84. Prior OAC use increased: in 2009, 67% were not on OACs but by 2018, one third used warfarin, one third direct OACs, and only one third were without any OAC. No association was found between anticoagulation and HS case fatality.
Conclusions: Among the population with incident AF, we observed a stable first-ever HS incidence rate and short-term case fatality over the past decade despite a marked increase in prior oral anticoagulation use and aging.